Innovative bulls eye drop applicator for self-instillation of eye drops. Issue 3 (June 2020) - Taneja, Mukesh; Chappidi, Kiranmayi; Harsha Ch, Sai Naga Sri; Richhariya, Ashutosh; Mohamed, Ashik; Rathi, Varsha M.
Highlights: Bulls Eye Drop applicator. Accurate self-instillation of eye drops. Innovative pocket size mirror-based attachment. Detachable for multiple uses. Abstract: Purpose: To report the role of Bulls eye drop applicator device in self-instillation of eye drops and in prevention of wastage of medicine. Methods: A small pocket sized device "Bulls eye drop applicator" was developed, which is a simple, handy, mirror-based attachment which can be attached to any eye drop bottle to help in accurate self-instillation of the drops in the eye. The prototype of this device was tried in ten volunteer subjects (Group 1) and 15 patients (Group 2); they were asked to use lubricating eye drops (5 ml bottle) in one eye without the device (N) and in the other eye with the device (M). The numbers of attempts for the application of eye drops were noted and the residual eye drops in the returned bottles were measured for quantitative assessment. Results: Ten volunteers and 11/15 patients completed the study. At the completion of the study, there were a total of 232 applications of eye drops in the Group 1 N (without device) and 1 M (with device). To achieve these 232 applications, there were 330 attempts without the device and 266 attempts of instillation were needed with the device (P < 0.0001). In Group 2, there were a total of 544 applications of eye drops; to achieve this, there were 879 attempts in Group 2 N and 685 attempts of instillation in Group 2 M (p < 0.0001). The cumulative quantity of residual drops in the returned bottles collected from Group 2 N was 5.1 ml and it was 19.7 ml in Group 2 M (p = 0.001). Conclusions: The number of attempts of instillation reduced significantly with the use of the eye drop applicator device. The use of eye drops applicator device reduced the wastage of drops from 42.2% to 14.6% in Group 1 N Vs Group 1 M and saving of about 35.7 % in Group 2 M compared to Group 2 N.